Emergency Powers and the Rule of Law - Yusof, Mohd Ariff (Journal of Malaysian and Comparative Law, 2019)
The rule of law and emergency powers lead an unhappy co-existence; the first is a principle of wide application which has as its overall purpose the subjection of government acts to defined legal criteria so as to avoid the toleration of arbitrary power, while the second consists of rules of principles with the avowed aim of supplying government with extremely broad powers in situations of crisis. Rule of law, as ordinarily understood, serves a limiting function, namely to ensure that government is conducted in accordance with accepted democratic norms. It is the very antithesis of arbitrary government, and once accepted as a basic feature of a constitutional system, no governmental power can be seen as lying beyond the pale of law.